2019
DOI: 10.1111/dmcn.14442
|View full text |Cite
|
Sign up to set email alerts
|

Participation of children with disabilities across the life course: using socio‐ecological perspectives to guide research and practice

Abstract: This commentary is on the original article by Arakelyan et al. on pages 445–453 of this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Identifying associated factors may help implement targeted interventions. To date, research on the factors associated with the participation of children with disabilities has been primarily conducted in developed countries, such as the US [13,14], Canada [15,16], and some European countries [17]. Corresponding research has revealed the essential impact of environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying associated factors may help implement targeted interventions. To date, research on the factors associated with the participation of children with disabilities has been primarily conducted in developed countries, such as the US [13,14], Canada [15,16], and some European countries [17]. Corresponding research has revealed the essential impact of environmental factors.…”
Section: Introductionmentioning
confidence: 99%